Only tomorrow: Delayed effects of teachers attitude on motor skill learning. (December 2022) - Awad-Igbaria, Yaseen; Maaravi-Hesseg, Rinatia; Admon, Roee; Karni, Avi
Abstract: Motor skill tasks provide unique opportunities to examine the impact of teachers' feedback on learners' performance, as the quality and quantity of motor behavior can be objectively assessed during the practice session (online-gains) and afterwards (delayed, offline-gains). We tested the learning and overnight retention of a newly instructed movement sequence in young healthy adults in three conditions of teacher-learner interaction, determined by the feedback afforded by the teacher: Indifferent-minimal (IM), General-encouragement (GE), Positive-social-comparison (PSC). All three conditions resulted in robust within-session gains in speed with no loss of accuracy. However, overnight, most trainees in the GE and PSC groups, but not in the IM group, expressed additional delayed gains. PSC group also exhibited feedback-induced increase in positive mood, which was correlated with their delayed gains. These results indicate that teacher-learner interactions during the learning session can affect long-term skill by modulating memory consolidation processes, even when within-session gains are unaffected. Highlights: Teachers' feedback is a powerful factor affecting skills and motor learning. Minimal teacher-learner interaction does not impair short-term learning. Positive social comparison feedback enhances positive mood and long-term learning.